2017
DOI: 10.1002/2017ja024439
|View full text |Cite
|
Sign up to set email alerts
|

Swarm Observation of Field‐Aligned Currents Associated With Multiple Auroral Arc Systems

Abstract: Auroral arcs occur in regions of upward field‐aligned currents (FACs); however, the relation is not one to one, since kinetic energy of the current‐carrying electrons is also important in the production of auroral luminosity. Multiple auroral arc systems provide an opportunity to study the relation between FACs and auroral brightness in detail. In this study, we have identified two types of FAC configurations in multiple parallel arc systems using ground‐based optical data from the Time History of Events and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 44 publications
(63 reference statements)
2
28
0
1
Order By: Relevance
“…This serves as a bound on the raw uncertainty in the magnetometer measurements, which translates to ∼2-μA/m 2 uncertainty in current density (under typical sheet-like current structure assumptions) for the 0.1-Hz sampling rate. While this uncertainty is large compared to those obtained with a scientific grade magnetometer, it is small compared to current densities observed in specific case studies of active aurora (e.g., Stasiewicz & Potemra, 1998;Wu et al, 2017).…”
Section: Figures 3a and 3bmentioning
confidence: 81%
See 1 more Smart Citation
“…This serves as a bound on the raw uncertainty in the magnetometer measurements, which translates to ∼2-μA/m 2 uncertainty in current density (under typical sheet-like current structure assumptions) for the 0.1-Hz sampling rate. While this uncertainty is large compared to those obtained with a scientific grade magnetometer, it is small compared to current densities observed in specific case studies of active aurora (e.g., Stasiewicz & Potemra, 1998;Wu et al, 2017).…”
Section: Figures 3a and 3bmentioning
confidence: 81%
“…The main progenitors for the present study are the ST‐5 (Slavin et al, ) and SWARM (Gillies et al, ; Ritter & Lühr, ) missions. For both missions, studies involving auroral arc crossings have revealed substantial space‐time variability in FACs, even under quiet conditions (Cumnock et al, ; Wu et al, ). The sensors used in the present study are lower quality “engineering grade” magnetometers, but the sheer number of sensors available in the Planet constellation (presently ∼200) poses interesting questions about trade‐offs between sensor capability, network density, and network coverage.…”
Section: Discussionmentioning
confidence: 99%
“…For both cases we show the multiscale FAC density and compare the scale integrated FAC density with the input FAC density. The simple case of a pair of FACs resembles the large scale R1/R2 system, as well as, the basic cell of a multiple arc system (Gillies et al, 2014;Wu et al, 2017). In the second case, the embedded smaller scale superposition can be associated to the analysis of the auroral oval with embedded smaller scale FACs, e.g.…”
Section: Synthetic Fac Structuresmentioning
confidence: 99%
“…The relation between multiple arc systems and their FAC signatures was addressed recently by (Wu et al, 2017) based on Swarm/THEMIS ASI observations. Wu et al (2017) selected events with clearly identifiable stable arcs and separated the observations in two categories, unipolar (multiple arcs embedded into a single large upward FAC) and multipolar events (a collection of multiple arcs and related pairs of upward and downward FACs). Arcs associated with multipolar FAC events were found to be broader and more separated than those associated with unipolar FAC events.…”
Section: Small Scale Auroral Observations Embedded Into a Large Scalementioning
confidence: 99%
See 1 more Smart Citation